The Influence of Principal Leadership and Teacher Motivation to Improve Student Learning Achievement in Public Elementary Schools - Hartini; Musdiani; Rahmatullah (Universitas Veteran Bangun Nusantara, 2024)
This research aims to analyze the influence of principal leadership and teacher motivation to improve student learning achievement in State Elementary Schools in Batee District. This research uses a quantitative approach, this type of research uses correlation research methods. This research used 125 samples by dividing them into each elementary school in Batee District. Data collection in this research used questionnaires and documentation. Data analysis in this research used the SPSS version 26 program. In this research, validity tests, reliability tests, classical assumption tests, multiple linear regression tests, hypothesis tests and coefficient of determination tests (R2) were used. The research results prove that the principal's leadership partially has a significant effect on student learning achievement. Teacher work motivation partially has a significant effect on student learning achievement. The principal's leadership and teacher work motivation simultaneously have a significant effect on student learning achievement.